2016
DOI: 10.1016/j.envpol.2016.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated diphenyl ethers (PBDEs) and alternative brominated flame retardants (aBFRs) in sediments from four bays of the Yellow Sea, North China

Abstract: a b s t r a c tThe distribution characteristics and potential sources of polybrominated diphenyl ethers (PBDEs) and alternative brominated flame retardants (aBFRs) were investigated in 54 surface sediment samples from four bays (Taozi Bay, Sishili Bay, Dalian Bay, and Jiaozhou Bay) of North China's Yellow Sea. Of the 54 samples studied, 51 were collected from within the four bays and 3 were from rivers emptying into Jiaozhou Bay. Decabromodiphenylethane (DBDPE) was the predominant flame retardant found, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 50 publications
7
27
2
Order By: Relevance
“…This suggests that the trend of consuming PBDEs exhibited a slight decline, whereas the usage of aBFRs, especially DBDPE, showed an increasing trend. It should be noted that concentrations of DBDPE in most sediments were higher than the levels of BDE 209, and this phenomenon was also observed in other studies of marine sediments and soils in China (Zheng et al, 2015;Zhen et al, 2016). Compared with BDE 209 and DBDPE, relatively low concentrations of S 7 PBDEs (mean of 20.4 pg g À1 dw), S 6 aBFRs (mean of 60.2 pg g À1 dw), and DPs (mean of 18.2 pg g À1 dw) were observed in this study.…”
Section: Concentration and Comparison Of Hfrs In The Sedimentssupporting
confidence: 76%
See 1 more Smart Citation
“…This suggests that the trend of consuming PBDEs exhibited a slight decline, whereas the usage of aBFRs, especially DBDPE, showed an increasing trend. It should be noted that concentrations of DBDPE in most sediments were higher than the levels of BDE 209, and this phenomenon was also observed in other studies of marine sediments and soils in China (Zheng et al, 2015;Zhen et al, 2016). Compared with BDE 209 and DBDPE, relatively low concentrations of S 7 PBDEs (mean of 20.4 pg g À1 dw), S 6 aBFRs (mean of 60.2 pg g À1 dw), and DPs (mean of 18.2 pg g À1 dw) were observed in this study.…”
Section: Concentration and Comparison Of Hfrs In The Sedimentssupporting
confidence: 76%
“…Furthermore, studies have reported that the atmosphere around Laizhou Bay and Weifang contained significant amounts of BDE 209 and DBDPE, which can be attributed to the point sources of local factories (Zhao et al, 2013;Lin et al, 2013). Zhen et al (2016) showed that the BFRs in the sediments of the coastal YS (Sisili Bay and Taozi Bay) were greatly affected by land-based emissions via coastal current transport. Coincidently, the contaminant concentration of NY3 was high in this study, as it is adjacent to the two Bays, indicating that these pollutants were transported from BS.…”
Section: Concentration and Comparison Of Hfrs In The Sedimentsmentioning
confidence: 99%
“… 107 110 These high levels of BDE-209 were found around BFR manufacturing areas, urbanized cities, and areas with numerous electrical factories. 108 In all mangrove sediments in Hong Kong, the concentrations of BDE-209 (ranged from 1.53 to 75.9 ng g –1 dw) were 1–2 orders of magnitude higher than those of other congeners in the same sediment, and the mangrove swamps are severely influenced by the pollution from the Pearl River Delta. 111 From the coastal East China Sea, extending about 1000 km from the Yangtze River Estuary to the south, the levels of BDE-209 were 0.3 to 44.6 ng g –1 dw, which were consistent with the current and historical usage of the decaBDE mixture in China.…”
Section: Bde-209 Pollution Status In Different Regions Of Chinamentioning
confidence: 95%
“… 75 In 2016, Zhen et al determined that Dalian Bay, which is located in the intersection of the Bohai Sea and Yellow Sea, exhibited a concentration (3.94–103 ng g –1 dw) of BDE-209 as was observed in surface sediments. 77 This is likely due to the presence of the electronics industry in Dalian city since the 1980s, and BDE-209 could also have been transported from the manufacturing bases in Laizhou Bay.…”
Section: Bde-209 Pollution Status In Different Regions Of Chinamentioning
confidence: 99%
See 1 more Smart Citation